2004
DOI: 10.1530/rep.1.00118
|View full text |Cite
|
Sign up to set email alerts
|

Components of litter size in mice after 110 generations of selection

Abstract: The aim of the present study was to evaluate how ovulation rate and survival rate through pregnancy had been affected by more than 110 generations of upwards selection on litter size in mice. The mean number of pups born alive was 22 in the high line (selected line) and 11 in the control line (an increase in 2.6 standard deviations). Selection on litter size increased ovulation rate by 4.6 standard deviations, and it is suggested that selection also increased embryonic mortality in late pregnancy. Embryo survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 21 publications
3
20
0
1
Order By: Relevance
“…Two very long-term selection experiments were carried out, one (experiment 1) without LS standardization (Dummerstorf, Germany;Schü ler 1982;Renne et al 1998;Langhammer & Renne submitted), and the other (experiment 2) with LS standardization (Å s, Norway; Joakimsen & Baker 1977;Vangen 1993;Holt et al 2004). In experiment 1, selection occurred for more than 130 generations (G) using an index combining LS0 and litter weight (LW0) at birth (IZ1.6 LS0CLW0).…”
Section: (C) Inbreeding Effectsmentioning
confidence: 99%
“…Two very long-term selection experiments were carried out, one (experiment 1) without LS standardization (Dummerstorf, Germany;Schü ler 1982;Renne et al 1998;Langhammer & Renne submitted), and the other (experiment 2) with LS standardization (Å s, Norway; Joakimsen & Baker 1977;Vangen 1993;Holt et al 2004). In experiment 1, selection occurred for more than 130 generations (G) using an index combining LS0 and litter weight (LW0) at birth (IZ1.6 LS0CLW0).…”
Section: (C) Inbreeding Effectsmentioning
confidence: 99%
“…As the selection aimed toward large litters, it can be suggested that an overall growth in body weight of the dams might be helpful for proper delivery. A rise in dam body weight during the selection period has also been noticed in the Norwegian high-FL (Holt et al 2004).…”
Section: Bias During Breeding Protocolmentioning
confidence: 57%
“…Nevertheless, independent of the fertility strategy selected by the particular mouse line, the improved fecundity lines deliver a substantially higher number of offspring per litter in comparison with Ctrl animals (Table 1). Interestingly, a significantly increased rate of gestational losses (as observed for FL1) has also been described for the Norwegian high-FL (Holt et al 2004). Moreover, the majority of gestational losses in FL1 animals occur during the first 4 days of pregnancy (Spitschak et al 2007).…”
Section: Characterization Of the Fls Fl1 And Fl2 On The Female Sidementioning
confidence: 58%
See 2 more Smart Citations